The answer is: " y − 1 = - 3(x + 2) " .
__________________________________________________________
Explanations:
__________________________________________________________
Note: The "point-slope form" of the equation of a line is:
→ " y − y₁ = m(x −x₁) " .
We are given the slope, m" , is: " - 3 " ;
We are given a point on the line [on the graph that is represented by this equation]; with the coordinates: " (-2 , 1) " ;
→ which is in the format: " (x₁ , y₁) " ;
→ As such: " x₁ = -2 " ; " y₁ = 1 " ;
_____________________________________________________
As aforementioned, the equation of a line in "point-slope form" ; is:
_________________________________________________________
→ " y − y₁ = m(x − x₁) " ;
in which:
→ "(x₁ , y₁) " represents the coordinates of a given point on the [line of the graph represented by the equation] ; AND:
→ " m " = the slope of the line [represented by the equation] " ;
We proceed by substituting our known values for "m" ; "y₁" ; and "x₁" :
→ " y − 1 = - 3(x − (-2) ) " ;
_______________________________________________________
→ Rewrite as:
_______________________________________________________
→ " y − 1 = - 3(x + 2) " ;
→ which is our answer; since it is written in "point-slope form" .
_______________________________________________________